The Privacy Paradox: Legal And Ethical Challenges In Hospital Data Security - Tiwari, Bincy Pothen; Baghel, Simran; Choudhary, Mahima; Thapa, Diya; Negi, Shalini; Neeraj, Neeraj; Rawat, Rajesh; Negi, Jitendra Singh (Journal of Neonatal Surgery, 2025)
Hospitals are being entrusted with enormous quantities of private patient data as the digital revolution of healthcare picks speed. Conversely, this increasing reliance on digital systems results in a paradox: the need to guarantee compliance with strict legal and ethical criteria at the same time requires improvement of data security. This study explores the intricate junction of data privacy, legal obligations, and ethical concerns in the framework of healthcare environments. Included are a review of the efficacy of present legal actions and a discussion of well-publicized data breaches. It also explores the problems that growing technology brings about. From a critical standpoint, this study identifies flaws in current methods and suggests fixes to balance fulfilling compliance criteria with safeguarding of personal privacy and encouraging of innovation.